Estudio para la Creación de un Centro de Entretenimiento Infantil y Familiar reactivando los Juegos Tradicionales del Ecuador, en la Ciudad de Ambato, Parroquia Urbana Atochaficoa. Centro de Eventos Chikii's Park - Villacrés Hidalgo, Cindy Pamela (2013)
Chikii's Park, is a small business that offers the rental of entertainment lounge with swings, slides, seesaw and interaction of animation using traditional folk games, offering food as an additional service with several options for children and adults and also the ease of acquiring invitations, candy, cake and special decoration of the room. This project proposes the development of a feasibility study, which looks at the early stages of jurisdiction, meet prospective clients and market behavior today. Subsequently, defining the characteristics of the company and the mission, vision, goals, objectives, principles, organizational structure, human resource function’s and operational activities. Finally known by studying accounting - financial business get positive results with a return rate of 62%, maintaining sustainable profitability over time. As a result of the project, the children's segment of the city of Ambato company will have a children's event planning through family integration mode in rescuing and implementing animation celebration, traditional games of yesteryear, as a way to promote and rescue Ecuadorian folklore and heritage in the urban parish Atocha - Ficoa. The property is located 15 minutes from the center of the city of Ambato on Los Guaytambos Avenue.